The use of rompun for transport of wild animals - Bongso, Tuan Ariffeen (Ceylon Veterinary Association, 1977)
Rompun was used at the recommended dosages for sedation of spotted deer (Axis axis), Sambur (Cervus unicolor) and the Wild boar (Sus scrofa) for the purpose of transportation by truck over a distance of 75 miles, which was to last 4 hours. It is evident from the results that the drug cannot be recommended for the restraint of the spotted deer because of the very nervous temperament of this species and consequent poor response to sedation. Maximum dosage of the drug on the wild boar resulted in no observable {fleets. The sambur responded best with 3 to 4 ml, being the sedative dosage of a 2% Rompun solution for an adult stag. The sedation period lasted approximately 4 hours.